Mechanical Properties of WC-Si3N4 Composites With Ultrafine Porous Boron Nitride Nanofiber Additive - Cao, Ting; Li, Xiaoqiang; Li, Jingmao; Huang, Yang; Qu, Shengguan; Yang, Chao; Liang, Liang; Song, Tao (Frontiers in Materials, 2021)
WC-10 wt.% Si3N4 composites toughened with ultrafine porous boron nitride nanofiber were prepared for the first time by spark plasma sintering. Typically, a second phase or additive is added for hardening or toughening because Young's modulus is a relatively stable property following the rule of mixtures. However, ultrafine porous boron nitride has an additional effect on improving Young's modulus on the composites.The obtained WC-10 wt.% Si3N4 with 0.05 wt.% ultrafine porous boron nitride was found to possess considerably high Young's modulus (779 GPa, which was even higher than densified WC bulk) in addition to good hardness (20.56 ± 0.87 GPa) and fracture toughness (10.57 ± 0.38 MPa•m 1/2 ). In addition, the Si3N4 phase did not exhibit traditional catastrophic fracture as indicated in most investigations. In this study, the peculiar phenomena are discussed, and a probable mechanism is elucidated. It is deduced that the approach of enhancing Young's modulus could be extended to materials with a feature of internal liquid phase during the sintering process and could improve fracture toughness.